2016
DOI: 10.1016/j.msec.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity response of Ta 1-x O x coatings deposited by reactive DC magnetron sputtering

Abstract: The use of dental implants is sometimes accompanied by failure due to periimplantitis disease and subsequently poor esthetics when soft-hard tissue margin recedes. As a consequence, further research is needed for developing new bioactive surfaces able to enhance the osseous growth. Tantalum (Ta) is a promising material for dental implants since, comparing with titanium (Ti), it is bioactive and has an interesting chemistry which promotes the osseointegration. Another promising approach for implantology is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Tantalum promotes bone ingrowth by establishing osseoincorporation that will enhance the secondary stability of implants in bone tissue and is more osteoconductive than titanium or cobalt-chromium alloys. [123] Oxidized Ta-based coatings were deposited by reactive DC magnetron sputtering onto Ti CP substrates in an Ar + O 2 atmosphere [124]. Bioactivity tests demonstrated that highest O-content coating showed an increased affinity for apatite adhesion, with higher Ca/P ratio formation, when compared to the bare Ti substrates.…”
Section: Nanostructured Surface Modificationsmentioning
confidence: 99%
“…Tantalum promotes bone ingrowth by establishing osseoincorporation that will enhance the secondary stability of implants in bone tissue and is more osteoconductive than titanium or cobalt-chromium alloys. [123] Oxidized Ta-based coatings were deposited by reactive DC magnetron sputtering onto Ti CP substrates in an Ar + O 2 atmosphere [124]. Bioactivity tests demonstrated that highest O-content coating showed an increased affinity for apatite adhesion, with higher Ca/P ratio formation, when compared to the bare Ti substrates.…”
Section: Nanostructured Surface Modificationsmentioning
confidence: 99%
“…A complete structural analysis of the coatings was previously performed and can be found in previous publication [18]. Briefly, Xray diffraction analysis showed three fundamental behaviors: (i) Ta1 coating revealed a crystalline body-centered cubic phase (bcc), characteristic a-Ta phase; when the oxygen content increases to 11 at.…”
Section: Coatings Chemical Structural and Morphological Characterizationmentioning
confidence: 99%
“…However, Ta presents higher prices and density comparatively with other metals [15,17]. Hence, the objective of this work is to coat stainless steel 316L (SS 316L) with Ta 1-x O x films to combine the enhanced bioactivity of Ta-based materials [18] with the low cost of SS 316L and evaluate the system corrosion resistance in artificial saliva.…”
Section: Introductionmentioning
confidence: 99%
“…Anodized Tantala is typically used in capacitors and as protective coating material for chemical equipment (e.g. optical devices) [19], but is also used in medical devices due to its enhanced bioactivity [20]- [23]. In addition, due to its excellent dielectric properties, it seems to be also an excellent option in electronic and sensor devices [19], [24], [25].…”
Section: Introductionmentioning
confidence: 99%